2013
DOI: 10.1080/00223131.2013.796897
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of size-controlled CeO2microparticles by a microfluidic sol–gel process as an analog preparation of ceramic nuclear fuel particles

Abstract: In this study, microfluidics integrated with sol-gel processes are introduced in preparing monodisperse ceramic nuclear fuel microspheres using nonactive cerium as a surrogate for plutonium. Detailed information about microfluidic devices and sol-gel processes used in the research is also provided. The effects of the viscosity and flow rate of the continuous and dispersed phase on the size and size distribution of CeO 2 microspheres were investigated. A comprehensive characterization of the CeO 2 microspheres … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…Due to the calcination, they are partially aggregated together. It is noteworthy that this technique allows the preparation of nanoparticles within 60 nm at 1000°C, which are much smaller compared with other physical or chemical methods that without stabilizers or surfactants (those are mostly larger than 100 nm and may reach micro-size level) [19,20]. Since conventional wet chemistry methods use supersaturated alkali precipitants, cerium hydroxides easily nucleate and grow to a large extent due to the vigorous hydrolyzing reactions.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the calcination, they are partially aggregated together. It is noteworthy that this technique allows the preparation of nanoparticles within 60 nm at 1000°C, which are much smaller compared with other physical or chemical methods that without stabilizers or surfactants (those are mostly larger than 100 nm and may reach micro-size level) [19,20]. Since conventional wet chemistry methods use supersaturated alkali precipitants, cerium hydroxides easily nucleate and grow to a large extent due to the vigorous hydrolyzing reactions.…”
Section: Resultsmentioning
confidence: 99%
“…However, evaluating the use of different types of oxide materials or microparticles as noble matrices requires a clear understanding of the mechanisms of defect formation, as well as their evolution as a result of high dose loads. The need to obtain such data opens up great prospects for researchers in this direction, and obtaining new data on the radiation resistance of inert matrices [21][22][23][24], as well as structural changes arising under the influence of radiation, can further be used to develop the theory of radiation materials science and expand the base of structural materials.…”
Section: Introductionmentioning
confidence: 99%
“…The main purpose of this work is to study the effect of Y 2 O 3 doping of CeO 2 microparticles on the resistance to swelling and structural degradation resulting from irradiation with heavy Xe 22+ ions. CeO 2 microparticles, which are currently one of the most promising materials of inert matrices for nuclear fuel [23,24], were chosen as the object of study [23,24]. The choice of Xe 22+ heavy ions with an energy of 225 MeV and an irradiation fluence of 10 15 ions/cm 2 allowed simulating the processes of radiation damage comparable to the impact of uranium fission fragments in a nuclear reactor at an atomic displacement value of 1-5 dpa.…”
Section: Introductionmentioning
confidence: 99%
“…However, the production rate of that technique was too low, and larger diameters were not obtainable. A more recent effort on microfluidic sol-gel process [2] demonstrated that cerium dioxide (CeO 2 ) microspheres could be produced over a much wider size range. However, no information on the production rate was provided.…”
Section: Introductionmentioning
confidence: 99%